PERAN WORK FROM HOME DAN WORK LIFE BALANCE TERHADAP PRODUKTIVITAS KERJA. - Ricky Adrianto Satria Wibowo; Salim Siregar (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
During the COVID-19 pandemic, most activities are not done face-to-face, so many aspects of life have changed. One of the most noticeable changes is the place of work. The place of work is one of the factors that contribute to work productivity. In addition, the COVID-19 pandemic has also changed the work system from working in the office to working from home with the aim of breaking the chain of COVID-19 spread. Changes that occur require employees to be able to realize a work-life balance so that work life and personal life are not disturbed. The purpose of this research is to know the role of work from home and work-life balance on work productivity. The methodology used by researchers in this study is a qualitative method with analysis techniques of literature studies from various sources (journals, books, internet) through traditional reviews. This means researchers used previous studies with the same variables as sources and basic references for improvisation. The results of this study can be concluded that the role of work from home on work productivity is not significant, while the work-life balance has a positive and significant role on work productivity.